2022
DOI: 10.1590/1413-785220223002240572
|View full text |Cite
|
Sign up to set email alerts
|

Undenatured Collagen Type Ii for the Treatment of Osteoarthritis of the Knee

Abstract: Objective: To test the hypothesis that undenatured type II collagen (UC-II) relieves pain, quality of life, and joint function in women aged from 60 to 80 years with knee osteoarthritis. Methods: 53 patients in the UC-II treatment group (for 90 days) and 52 in the control group (without UC-II) were evaluated at 1, 30, and 90 days regarding health-related quality of life, pain, and function with questionnaires, anthropometric data, alignment, range of motion, and radiographic analysis. Results: Quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…Many animal [22][23][24][25] and human 18,26,27 studies have demonstrated a beneficial effect of undenatured collagen administration on OA; however, the effects of undenatured collagen in different doses and age groups have not been investigated. The present study is the first to compare the efficacy of different doses of undenatured collagen on MIA-induced OA in young and old rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many animal [22][23][24][25] and human 18,26,27 studies have demonstrated a beneficial effect of undenatured collagen administration on OA; however, the effects of undenatured collagen in different doses and age groups have not been investigated. The present study is the first to compare the efficacy of different doses of undenatured collagen on MIA-induced OA in young and old rats.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that OA treatment using undenatured collagen alleviates joint pain and improves quality of life 27 . Although a low dose of undenatured collagen did not effectively attenuate joint cartilage damage in old rats, the present findings show that all doses of undenatured collagen supplementation reduced knee swelling and improved gait patterns, closely related to pressure pain thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…(2022 г.) [26] НК-II изучен у пожилых пациентов (60-80 лет) с ОА, осложненным различными проявлениями метаболического синдрома. Ввиду сложности выбора симптом-модифицирующей терапии для коморбидных пациентов с ограничениями к назначению или прямыми противопоказаниями для назначения НПВП (СД, неконтролируемая АГ, хроническая болезнь почек) возможность применения у них исследуемой комбинации имеет важное практическое значение.…”
Section: Discussionunclassified
“…Up to date, several clinical trials regarding the use of collagen as a food supplement for joint health have been published. Most of the studies have evaluated the therapeutic potential of either native type II collagen [ 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ] or hydrolyzed collagens [ 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ] in patients with OA. However, both types of collagens have been also tested in non-osteoarthritic individuals suffering joint discomfort [ 108 , 109 , 110 , 111 , 112 , 113 ].…”
Section: Clinical Evidencementioning
confidence: 99%